2022
DOI: 10.1021/acs.iecr.2c01168
|View full text |Cite
|
Sign up to set email alerts
|

Promoting Effect of Ni on the Catalytic Production of Alanine from Lactic Acid over RuNi/AC Catalyst

Abstract: A series of RuNi bimetallic catalysts supported on activated carbon were prepared to study the reductive amination of lactic acid. Among the tested catalysts, the catalyst containing 40% Ni and 60% Ru was selected as the optimal catalyst. The yield of alanine significantly increased to 64% using the Ru6Ni4 catalyst supported on an activated carbon, which was 1.5 times that using the monometallic Ru catalyst supported on an activated carbon. A number of characterization methods such as transmission electron mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 51 publications
0
4
0
Order By: Relevance
“…The H 2 -TPR profiles of Ru-based catalysts are shown in Figure . For the 2Ru/NiAl 2 O 4 catalyst, three H 2 consumption peaks appeared at 100, 164, and 405 °C, which are assigned to RuCl 3 , RuO 2 , and co-reduction of RuO x and NiO x species in NiAl 2 O 4 , respectively. , For the 2Ru1Ni/NiAl 2 O 4 catalyst, three peaks moved to higher temperatures (112, 183, and 416 °C, respectively) due to the interaction between Ru and Ni. It is worth noting that a co-reduction peak of RuO x and NiCl 2 species (322 °C) was observed (a lower reduction temperature than 416 °C), suggesting that the interaction between RuO x and NiCl 2 species is weaker than that between RuO x and NiO x species in NiAl 2 O 4 .…”
Section: Resultsmentioning
confidence: 99%
“…The H 2 -TPR profiles of Ru-based catalysts are shown in Figure . For the 2Ru/NiAl 2 O 4 catalyst, three H 2 consumption peaks appeared at 100, 164, and 405 °C, which are assigned to RuCl 3 , RuO 2 , and co-reduction of RuO x and NiO x species in NiAl 2 O 4 , respectively. , For the 2Ru1Ni/NiAl 2 O 4 catalyst, three peaks moved to higher temperatures (112, 183, and 416 °C, respectively) due to the interaction between Ru and Ni. It is worth noting that a co-reduction peak of RuO x and NiCl 2 species (322 °C) was observed (a lower reduction temperature than 416 °C), suggesting that the interaction between RuO x and NiCl 2 species is weaker than that between RuO x and NiO x species in NiAl 2 O 4 .…”
Section: Resultsmentioning
confidence: 99%
“…Afterwards, extensive research efforts were devoted to develop highly efficient thermocatalytic systems for amino acid synthesis from α-hydroxyl acids. [49][50][51][52] For example, Xie et al reported that N-doped carbon nanotube-supported Ru nanoparticles (Ru/N-CNTs) exhibited a remarkable performance in the amination of lactic acid, in which the maximum alanine yield of 70% was obtained at 180 °C and 10 bar H 2 for 2 h. 52 The outstanding activity of the Ru/N-CNT catalyst was mainly attributed to the highly dispersed Ru nanoparticles, the strong electronic interaction between Ru nanoparticles and N-CNTs, and the enhanced adsorption of lactic acid through basic sites. Xin et al prepared a magnetic catalyst Ru/Ni@C by ethylene glycol reduction of metal Ru supported on encapsulated Ni@C. 51 The best catalytic performance was obtained with a lactic acid conversion of 70% and an alanine yield of 64% at 200 °C and 15 bar H 2 for 2 h. The formed RuO 2 species, acting as Lewis acid sites, could improve the activation of the hydroxyl group of lactic acid as well as the adsorption ability of NH 3 , accordingly facilitating the amination of lactic acid to alanine.…”
Section: Biological Synthesismentioning
confidence: 99%
“…Amino acids as the fundamental building blocks of life proteins have a wide range of application in various fields. In particular, alanine stands out as one of the most important amino acids and is widely utilized in food, agriculture, biodegradable plastics, and pharmaceutical industries. The current production of alanine is primarily relied on microbial cultivation processes, which is costly, time-consuming, and involves extensive separation processes, limiting their large-scale application. , Previous studies have developed different catalytic systems for the reductive amination of biomass-derived lactic acid to alanine in a H 2 atmosphere . For instance, Yan et al demonstrated that Ru/CNT was a highly effective catalyst for amination of lactic acid in ammonia, achieving a 62% yield .…”
Section: Introductionmentioning
confidence: 99%